AKUNTABILITAS KOMISI INFORMASI PROVINSI RIAU DALAM PENYELESAIAN SENGKETA INFORMASI PUBLIK TAHUN 2023-2024 - Saidori, Amanda; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
Disclosure Public information disclosure is one of the important principles in realizing good governance. The implementation of Law Number 14 of 2008 concerning Public Information Disclosure places the Information Commission as an institution authorized to resolve public information disputes through mediation mechanisms and non-litigation adjudication. However, in practice, information dispute resolution still faces various problems, such as low compliance by public bodies with decisions, dispute resolution that exceeds the 100-day working deadline, weak post-decision monitoring, and limited human resources and technical support. This condition shows that the accountability aspect in resolving public information disputes still needs to be strengthened. This research aims to find out and analyze the accountability of the Riau Provincial Information Commission in resolving public information disputes in 2023–2024. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through interviews, documentation, and literature studies. The research analysis uses accountability theory according to David Hulme and Mark Turner which includes six indicators, namely the legitimacy of policymakers, moral quality, responsiveness, openness, optimal use of resources, and efforts to improve efficiency and effectiveness. The results of the study show that the Riau Provincial Information Commission has carried out the function of resolving public information disputes through mediation mechanisms and non-litigation adjudication in accordance with the provisions of laws and regulations. However, accountability in dispute resolution is not fully optimal. This can be seen from the fact that there are still disputes that are resolved beyond the specified time limit, limited executive authority to force public bodies to implement decisions, weak post-decision monitoring and evaluation, and limited human resources and technical support. Therefore, it is necessary to strengthen cross-sector coordination, increase institutional capacity, and optimize the supervisory system to increase the effectiveness of resolving public information disputes and realize the principle of information disclosure in a more accountable manner. Keywords: Accountability, Information Commission, Public Information Disputes, Information Disclosure.